2020
DOI: 10.3934/dcdss.2020140
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a model of tumor-immune interaction with time delay and noise

Abstract: We propose a model of tumor-immune interaction with time delay in immune reaction and noise in tumor cell reproduction. Immune response is modeled as a non-monotonic function of tumor burden, for which the tumor is immunogenic at nascent stage but starts inhibiting immune system as it grows large. Without time delay and noise, this system demonstrates bistability. The effects of response time of the immune system and uncertainty in the tumor innate proliferation rate are studied by including delay and noise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This leads to the attempt of anti-tumor treatment by activating the immune system. Current studies (see [8,9] and reference therein) have shown that the immune system has specific and nonspecific responses to tumors, and its mechanism is very complex, involving a variety of immune cells and their secretory products. They interact, regulate and complement each other, and jointly complete the immune surveillance function.…”
Section: Introduction and Main Resultmentioning
confidence: 99%
See 4 more Smart Citations
“…This leads to the attempt of anti-tumor treatment by activating the immune system. Current studies (see [8,9] and reference therein) have shown that the immune system has specific and nonspecific responses to tumors, and its mechanism is very complex, involving a variety of immune cells and their secretory products. They interact, regulate and complement each other, and jointly complete the immune surveillance function.…”
Section: Introduction and Main Resultmentioning
confidence: 99%
“…In [6], the author proposed an ODEs model about tumor and immune effector. And then, the authors in [9] gave a special case of the model as follows…”
Section: Introduction and Main Resultmentioning
confidence: 99%
See 3 more Smart Citations